Effect of an Effective Strategic Planning for Organizational Performance of Prof.Dr.R. Soeharso of Orthopaedic Hospital of Surakarta - Yousef, Alsaidi Ab Alsaidi; , Dr. Amin Mustofa, M.HA; , Drs. Anton Agus Setyawan, SE., M.Si (2014)
The purpose of this study is determining the effect of the effective strategic planning at Orthopaedic Hospital of Prof.Dr.R. Soeharso Surakarta, influences on strategic planning on the performance of the organization at the Orthopaedic Hospital of Prof.Dr.R. Soeharso Surakarta and effective influence on strategic planning indirectly through the organization's performance in the Orthopaedic Hospital of Prof.Dr.R. Soeharso Surakarta. This research is quantitative, by taking samples at Orthopaedic Prof.DR.R. Soeharso of at Jl. A. Yani, Pabelan, Kartasura, Surakarta, Central Java, Indonesia, 57162. Out of 678 employees, 70 employees are taken for the study of population and sample. Questionnaires are used as the technique of collecting data whereas path analysis has been used as the data analysis technique. The results obtained showed that the positive effect on effective strategic planning, strategic planning has a positive effect on organizational performance, and no effective strategic planning on organizational performance indirectly through employee benefits in Prof.DR.R. Soeharso of Orthopaedic Surakarta. This is proved by the results of the analysis which states that effective relationships with organizational performance otherwise has no direct relationship through strategic planning.